Anthropology on the move : contextualizing culture studies in Bangladesh - Islam, Zahidul; Shafie, Hasan; University of Dhaka. Department of Anthropology (Dhaka : University of Dhaka, 2006)
Contributed articles presented in a conference at University of Dhaka, January, 2005.
Includes bibliographical references.
Keywords: Anthropology -- Bangladesh -- Congresses; Ethnology -- Bangladesh -- Congresses